The returns of fetishism: Charles de Brosses and the afterlives of an idea - Morris, Rosalind C. (The University of Chicago Press, 2017)
Contents -- "Fetishism (Supposing That It Existed)": A Preface to the Translation of Charles de Brosses's Transgression - Rosalind C. Morris -- Introduction: Fetishism, Figurism, and Myths of Enlightenment - Daniel H. Leonard -- A Note on the Translation - Daniel H. Leonard -- On the Worship of Fetish Gods -- Or, A Parallel of the Ancient Religion of Egypt with the Present Religion of Nigritia - Charles de Brosses -- Translated by Daniel H. Leonard -- After de Brosses: Fetishism, Translation, Comparativism, Critique - Rosalind C. Morris -- A Fetiche Is a Fetiche: No Knowledge without Difference -- Of the Word: Rereading de Brosses -- Excursus: Recontextualizing de Brosses, with Pietz in and out of Africa -- Re: Kant and the Good Fetishists among Us -- Hegel: Back to the Heart of Darkness -- Fetishism against Itself -- or, Marx's Two Fetishisms -- The Great Fetish -- or, The Fetishism of the One -- Freud and the Return to the Dark Continent:The Other Fetish -- Conjuncture: Freud and Marx, via Lacan -- Anthropology's Fetishism: The Custodianship of Reality -- Fetishism Reanimated: Surrealism, Ethnography, and the War against Decay -- Deconstruction's Fetish: Undecidable, or the Mark of Hegel -- Rehistoricizing Generalized Fetishism: The Era of Objects -- Anthropological Redux: The Reality of Fetishism -- The Fetish Is Dead, Long Live Fetishism -- Acknowledgments -- Notes -- Bibliography -- Index.